Specialization in Bank Lending: Evidence from Exporting Firms - PARAVISINI, DANIEL; RAPPOPORT, VERONICA; SCHNABL, PHILIPP (Journal of Finance, 2023)
ABSTRACT We develop a novel approach for measuring bank specialization using granular data on borrower activities and apply it to Peruvian exporters and their banks. We find that borrowers seek credit from banks that specialize in their export destinations, both when expanding exports and when exporting to new countries. Firms experiencing country‐specific export demand shocks adjust borrowing disproportionately from specialized banks. Specialized bank credit supply shocks affect exports disproportionately to countries of specialization. Our results demonstrate that firm credit demand is bank‐ and activity‐specific, which reduces banking competition and affects the transmission and amplification of shocks through the banking sector.